Miskonsepsi Pengerjaan Operasi Deret Aritmatika PGMI 3 UIN Sumatera Utara - Nabila Ulkhaira; Rora Rizki Wandini (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This article analyzes the misconceptions in carrying out arithmetic series operations that occur among students in the PGMI 3 class at UIN North Sumatra. The method used in this research is descriptive qualitative with an observation approach and written tests. Regarding the problem formulation in this research, namely (1) what misconceptions about working on arithmetic series operations occur among PGMI 3 UIN North Sumatra students; (2) how can misconceptions about working on arithmetic series operations be detected among PGMI 3 UIN North Sumatra students; and (3) how many PGMI 3 UIN North Sumatra students are classified as understanding or not understanding the concept of working on arithmetic series operations. Regarding the research results, it shows that (1) misconceptions about working on arithmetic series operations can occur because students have low memory, understanding and accuracy; (2) misconceptions about working on arithmetic series operations can be detected because there are different answers between students; (3) the number of students who are classified as understanding the concept of working on arithmetic series operations is around 47% and students who do not understand the concept of working on arithmetic series operations is around 52%.